2018
DOI: 10.1051/matecconf/201815202014
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Flow Patterns over a Hierarchical and a Non-hierarchical Surface in Relation to Biofouling Control

Abstract: Biofouling can be defined as unwanted deposition and development of organisms on submerged surfaces. It is a major problem as it causes water contamination, infrastructures damage and increase in maintenance and operational cost especially in the shipping industry. There are a few methods that can prevent this problem. One of the most effective methods which is using chemicals particularly Tributyltin has been banned due to adverse effects on the environment. One of the non-toxic methods found to be effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was also found that with the increase of Re and the ratio of particle radius to microridge height, the number of deposited particles decreased. Bin Ahmad Fawzan et al [23] compared the antifouling performance of hierarchical and non-hierarchical topographies. Simulation results expressed that the range for wall shear of hierarchical topography is between 0.00281 Pa and 0.00452 Pa, while non-hierarchical topography is between 0.00165 Pa and 0.00301 Pa. Lee et al [24] studied the shear stress distribution on a prismatic surface by simulations and suggested that a high shear stress was generated on the surface of the prismatic structure; hence, shear stress was considered as the main antifouling factor of the microstructured surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that with the increase of Re and the ratio of particle radius to microridge height, the number of deposited particles decreased. Bin Ahmad Fawzan et al [23] compared the antifouling performance of hierarchical and non-hierarchical topographies. Simulation results expressed that the range for wall shear of hierarchical topography is between 0.00281 Pa and 0.00452 Pa, while non-hierarchical topography is between 0.00165 Pa and 0.00301 Pa. Lee et al [24] studied the shear stress distribution on a prismatic surface by simulations and suggested that a high shear stress was generated on the surface of the prismatic structure; hence, shear stress was considered as the main antifouling factor of the microstructured surface.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase of Re and a/h, an "inaccessible area" for suspended particles was formed near the surface of the microstructure membrane, thus reducing the deposition of particles. Fawzan et al [20] compared the antifouling performance of hierarchical and non-hierarchical topographies. Simulation results expressed that the range for wall shear of hierarchical topography is between 0.00281 Pa and 0.00452 Pa while non-hierarchical topography is between 0.00165 Pa and 0.00301 Pa. CFD was also applied to study the heat transfer characteristics of microstructures [21].…”
Section: Introductionmentioning
confidence: 99%